The Conceptual Comparison Between Vecdi Akyüz’s Work Titled Kur’an’da Siyasi Kavramlar and Manzooriddin Ahmad’s Work Titled Islamic Political System in the Modern Age: Theory and Practice - Ayşe Aytekin (Yakın Doğu Üniversitesi İlahiyat Fakültesi Dergisi)
In understanding and interpreting texts or religious messages with various contents, it is important matter to determine the focal concepts or keywords, the areas with which these words are related, and the characteristics of these areas, which are created with a new analysis style. It can be compensated the difference in understanding and signification between the period of the sacred text and the period of modern man, only in this way. In this manner, it is much more necessary and obligatory to analyze and understand the focal concepts in the process of understanding and making sense of the sacred texts, in which the divine messages that are desired to be conveyed to people are presented in various conceptual patterns, compared to other texts. As a matter of fact, to examine the meaning dimensions of the focal concepts in the Qur’ān correctly, which have connotations, as well as their basic dictionary meanings, and the new meanings they have gained in the context of the Qur’ān, and to explore the adventures of these terms successfully, are very valuable for both understanding and applying the message and in terms of its contribution to the science of tafsīr. Therefore, field and concept analysis is a necessity in the interpretation of the divine messages equipped with the concept weave together with the classical methods developed for the understanding of the Qur’ān during the History of tafsīr process and rich historical and scientific experience. The fact that tafsīr activities have uninterruptedly continued from the first periods to the present day is an indication and reflection of its necessity. Although times, places, periods, conditions, requirements, circumstances, and interpretations have changed during the history of tafsīr activity, the words, ideas, efforts, materials, and products in this activity are extremely necessary and important for the interpretation and needs of contemporary people. In the period following the privatization of tafsīr activities, methods and varieties the research and determination of the issues of the basic areas of life such as politics, culture, and economy’s influence on the products in question to what extent, in which phases they are beneficial, and in which phases they cause harm are valuable for a sound analysis the process of tafsīr study because, the basic features, elements, effects, and necessities of life must be examined to reach the divine purpose meticuoulsy, since they are included in the basic guide which is a divine word. Politics, which is one of the fields that should be studied meticulously, is one of the most important and active areas of life and one of the most influential institutions of societies. As a matter of fact, politics has the same care in the Islamic society as in the existence and power periods of other societies. As it has been associated with other institutions and fields in social life, the divine word has also found a place for itself in various issues. Politics is the subject that has been mainly dealt with in the interpretation activities of the Qur’ān both in the conditions of the revelation period and in the post-revelation period. In our study, we have aimed to analyzte the concepts and contexts in the Qur’ān and how it has been evaluated in two interrelated works that examine these concepts, together with our opinion that such an important issue should be investigated to lead a happy and peaceful life by obeying divine orders and rules. In this respect, two works that investigate the concepts related to politics in the perspective and plane of the Qur’ān are the subject of our study. These works are Vecdi Akyüz’s work titled Kur’an’da Siyasi Kavramlar and Manzooriddin Ahmad’s work titled Islamic Political System in the Modern Age: Theory and Practice. Although the authors of the works were born, had lived, had trained in different times, cultures and geographies, and had specialized in different fields, they had met on common ground in terms of examining and interpreting the concepts with political content in the Qur’ān. In our article, we have the purpose to examine the political terms in question in the context of divine speech and the interpretations of these two authors who have different areas of expertise.